Seroprevalence of dengue infection and associated factors in residents of Fila Alta village - Facundo Chinguel, Aydee (2021)
Objective. The objectives of the study were to determine the seroprevalence of dengue infection and to identify the associated factors in the residents of the Fila Alta village, district of Jaén, department of Cajamarca, during the months of September to December 2019. Methods. Observational, cross-sectional, prospective study with a non-experimental design with a descriptive-correlational approach. The sample consisted of 172 inhabitants of both genders and the sampling was simple random. The seroprevalence of IgG antibodies was determined by indirect enzyme-linked immunosorbent assay (ELISA) and a structured survey was applied to identify the factors associated with dengue. Likewise, the chi-square test was used to establish the relationship between the variables studied. Results. IgG antibodies to dengue fever were present in 19.2 % of the population, being more frequent in women (12.2 %). Dengue seropositivity was found in 9.3 % (OR: 0.18; PR: 0.16; 95 %CI: 0.09-0.23) of students and 5.8 % (OR: 0.31 PR: 0.24; 95 %CI: 0.11- 0.37) of housewives. In addition, 15.7 % (OR: 0.28; PR: 0.22; 95 % CI: 0.15-0.29) of seropositive villagers obtained their water supply from tanks and the most common material used in the construction of their houses was adobe (8.7 %; OR: 0.94; PR: 0.48; 95 % CI: 0.30-0.66). Conclusions. The seroprevalence of dengue infection is high and is signifcantly related to the occupation of the inhabitants and the material of the walls of their houses